أهم المحددات السيكو- سوسيولوجية المستخدمة في قياس وتشكيل سلوك العمال التنظيمي - عنصر, يوسف; ليتيم, ناجي (University of Eloued جامعة الوادي, 2014)
لقد جاء في أعقاب الثورة الصناعية العديد من التيارات والمدارس الفكرية والتنظيمية التي سعت إلى تعظيم أداء ومخرجات العمال داخل أرجاء المنظمات على تنوع أحجامها ونشطاتها وأهدافها، ولقد كان الإتفاق السائد بين مختلف المفكرين والمنظرين في ذلك الوقت أنه ما من سبيل لتلافي هذه المعظلة السوسيو-تنظيمية إلا من خلال الوقوف على تشريح وفهم وتفسير مكونات السلوكات العمالية، ولقد تمخض على إثر تلك الدراسات والأبحاث العلمية رصد وتشخيص لأهم المحكات والمحددات السوسيولوجية والسيكولوجية المعيارية التي يتوجب على العمال التقيد بها، والتي تتحكم في تشكيل سلوكياتهم، وتتخذ كمنطلقا ومرجعا لقياسها، وتأسيسا على ما تقدم فمحور هذا المقال ينصب حول تشخيص أهم المحكات والمحددات السوسيولوجية والسيكولوجية المعيارية التي تؤثر تأثيرا بالغا في بناء وتشكيل سلوكيات العمال التظيمية؟ Abstract : : At the end of the Industrial Revolution, many organizational and thoughtful schools came to life which sought to increase the productivity of workers within organizations in terms of their sizes, activities and goals, and it was agreed that the prevailing between the various thinkers and researchers at the time that there is no solution to this organizational problem, but only by the understanding, analyzing and interpreting workers’ behaviors. It has been resulted of those studies and scientific research the diagnosis of the most important determinants of the sociological and psychological normative workers which should be respected by these lasts. They control the formation of their behavior and considered as a reference for measuring them. From what we have seen above, we concluded that the article focuses on the diagnosis of the most important sociological and psychological normative determinants which has a great influence on the formation of workers' organizational behaviors. Keywords: social determinants, psychological determinants, workers, organizational behavior.
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: المحددات الإجتماعية - المحددات السيكولوجية - العمال - السلوك التنظيمي